2014
DOI: 10.1371/journal.pone.0104863
|View full text |Cite
|
Sign up to set email alerts
|

Low-Intensity Pulsed Ultrasound Induces Angiogenesis and Ameliorates Left Ventricular Dysfunction in a Porcine Model of Chronic Myocardial Ischemia

Abstract: BackgroundAlthough a significant progress has been made in the management of ischemic heart disease (IHD), the number of severe IHD patients is increasing. Thus, it is crucial to develop new, non-invasive therapeutic strategies. In the present study, we aimed to develop low-intensity pulsed ultrasound (LIPUS) therapy for the treatment of IHD.Methods and ResultsWe first confirmed that in cultured human endothelial cells, LIPUS significantly up-regulated mRNA expression of vascular endothelial growth factor (VEG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(72 citation statements)
references
References 35 publications
1
70
1
Order By: Relevance
“…Over the past 3 0 years, LIPUS has been used as a principal non-invasive therapy for effective promotion of healing of fractures [15] and regeneration of damaged peripheral nerves [16]. LIPUS has also been tested for its potential application to ameliorating left ventricular remodeling in mice with post-myocardial infarction [17]. However, the studies on the role of LIPUS in endothelial injury have been rather sparse.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past 3 0 years, LIPUS has been used as a principal non-invasive therapy for effective promotion of healing of fractures [15] and regeneration of damaged peripheral nerves [16]. LIPUS has also been tested for its potential application to ameliorating left ventricular remodeling in mice with post-myocardial infarction [17]. However, the studies on the role of LIPUS in endothelial injury have been rather sparse.…”
Section: Introductionmentioning
confidence: 99%
“…On one hand, iPSCs-NCSCs can differentiate into vascular cells and neurons, which could accelerate the vascular and nerve regeneration during the restore of injured nerve (Kane et al 2011). On the other hand, LIPUS could induce angiogenesis (Hanawa et al 2014) and promote neural differentiation (Lv et al 2013). In addition, LIPUS could speed up the exchanges of nutrients and toxic substances which are good for the formation of nerve filaments (Chen et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Many in vivo studies have demonstrated that LIPUS can be beneficial in improving healing in several other tissue types, including the skin wounds of diabetic and aged mice by increasing fibroblast migration into the wound site (Roper et al, 2015), ischemic heart disease by increasing angiogenesis (Hanawa et al, 2014), tendon repair (Jeremias Junior et al, 2011;Lu et al, 2016) by increasing collagen synthesis (Fu et al, 2010), and muscle repair after injury by increasing myofibre regeneration .…”
Section: Introductionmentioning
confidence: 99%